Public perception of e-money in the perspective of marketing communication strategy (Bandung) - Wirajati, Nugraha; S. Hariandja, Evo. (The Indonesian Journal of Business Administration, 2016)
Abstract - Gardenia Diary is a photography and videography business based in Bandung Indonesia, founded in 2010 and rebranded in late 2013, these company now focuses on wedding photography and videography but also deliver services to other type of work categories such as commercials, editorial and events. Wedding business in Bandung is high in competitive, there is a lot of similar vendor who serve similar services. While the traction and client are increasing but it is in a slow progress. Gardenia Diary monthly capacity projects is low, while most effort in advertising did not give a good result. Dependencies from wedding documentaries, which are seasonal, are making business revenue unstable. Gardenia Diary management realized that they needs to do improvement in marketing strategies. To create a new marketing plan strategy, the author did a quantitative research. The data from questionnaire will be combined with company situation, business situation and supported with company data. All of these data are used to discover the root cause of business problem and proposing business solution of Gardenia Diary. To achieve company goals, Gardenia Diary should improve its marketing mix. The proposed marketing plans are done to support and solve business problem, which mainly cover costumer relationship improvement, efficient marketing plan, and create a new differentiated products. To make it succeed, the implementation plan must apply correctly and under the supervision of owner or manager.Â Key Words: Marketing strategy, wedding documentary